Preparation and characterization of bacterial cellulose-beeswax films. (June 2018) - Indriyati,; Indrarti, L
Abstract: Bacterial cellulose (BC) based polymer films containing carboxymethyl cellulose (CMC) and beeswax as additives were produced. Control film was prepared by mixing of BC slurry and CMC, while treated films were produced by the addition of beeswax/Tween 80 solution in various concentrations. The objective of this work was to study the effect of beeswax content on properties of BC films. The films were prepared by solution casting technique and dried in convection oven at 40 °C overnight. Addition of beeswax dissolved in Tween 80 affected mechanical properties, significantly reducing the tensile strength but increasing elongation of the control film by 22 and 43%, respectively. Beeswax+Tween80 addition also improved water solubility by doubled from 36 to 73-78%. However, there was no significant difference of WVTR and hydrophobic properties among those films with the addition of beeswax in Tween 80 into the mixtures of BC slurry+CMC.